Boiler control systems engineering - Gilman, G. F. (International Society of Automation, 2010)
This book is for anyone who works with boilers: utilities managers, power plant managers, control systems engineers, maintenance technicians or operators. The information deals primarily with water tube boilers with Induced Draft (ID) and Forced Draft (FD) fan(s) or boilers containing only FD fans. It can also apply to any fuel-fired steam generator.
Keywords: Steam-boilers -- Automatic control.; elektronické knihy; electronic books